A study of net income and return on shareholder equity in Malaysia / Sharifah Norazita Wan Shazali - Wan Shazali, Sharifah Norazita (2003)
This Study is conducted to determine if there is any significant correlation between net income and earning per share, dividend per share and dividend payout ratio. Five samples from each five different sectors i.e. consumer products, properties, industrial products, trading/services and finance are randomly selected for the study. The sample period is from January 1999 to December 2002, a period after the Malaysian economy has recovered from recurrence of the 1997-1998 Asian economic crisis. In this study, net income has been chosen as a dependent variable and earning per share, dividend per share and dividend payout ratio as independent variables.